Effects of the long-acting analgesics 3-(b-phenylethyl)-9b-methoxy-9a-(m-hydroxyphenyl)-3-azabicycles [3,3,l]-nonane (P-7521) on opiate receptor binding in vitro - Zhou De-He; Ge Bang-Lun; Xu Xue-Jun; Chi Zhi-Qiang (Acta Pharmacologica Sinica, 2016)
After 6 washes, rat brain P2 membranes preincubated with P-7521 showed only a 15% recovery of [3H]etorphine binding activity. however P2 treated with morphine or 3-(b-phenylethyl)-9-dimethoxy-3-azabicyclo [3,3,1]-nonane (P-7520) yielded 100% recovery of binding activity after only 2 washes. Scatchard analysis of saturation experiments 16 h after P-7521 treatment in vivo still showed a lack of high affinity binding sites of [3H]etorphine. The binding activity of digitonin/MgSO4 soluble rat brain opiate receptors pretreated with P-7521 and then dialyzed against Tris-HCI buffer for 24 h to [3H]ohme-fentanyl was restored to about 63% of control. In conclusion, P-7521 binds tightly to rat brain opiate receptors.